Legal Consequences of Violation of the Right to be Heard in Administrative Proceedings - Hakobyan, Karen (Bulletin of Yerevan University C: Jurisprudence, 2024)
This scientific article is devoted to the comprehensive research of the legal consequences of violating the right to be heard in administrative proceedings, one of the important components of the right to good administration. The problematic situations that arise in this area were described using the following questions: (1) Should a violation of the right to be heard in all cases lead to the invalidity of an administrative act adopted with that violation? (2) After an administrative act adopted in violation of the right to be heard is declared invalid, can the administrative authority re-adopt the same administrative act, provided that the violation of the right to be heard is eliminated․As a result of the analysis of these issues, it was justified the need to develop and apply such new approaches and solutions regarding the legal consequences of violating the right to be heard of a participant in administrative proceedings, which will ensure, on the one hand, the protection of fundamental human rights, and, on the other hand, the effectiveness of public administration and the realization of public interests.
Keywords: administration; good administration; double administration; the right to be heard; administrative act; protection of human rights; effectiveness of the administrative authorities; public interest